Comparative Study of Oral versus Intravenous Iron Therapy in Patients of Chronic Renal Failure Receiving Recombinant Human Erythropoietin - Sadat Memon; Nasreen Qazi; Shafiq ur Rehman Memon; Jamil Laghari (JLUMHS, 2019)
OBJECTIVE: To evaluate the effects of oral and intravenous Iron on serum ferritin and total Iron binding capacity in patients of chronic renal failure receiving recombinant human erythropoietin. METHODOLOGY: This prospective comparative interventional study was conducted in the Department of Pharmacology and Therapeutics LUMHS Jamshoro with the collaboration of Urology Department of Liaquat University Hospital (LUH) Jamshoro and Hyderabad, for the duration of 6 months after approval from research ethics committee of the institute. By using Rao software sampling calculator and after following inclusion and exclusion criteria 80 patients were taken and divided into two groups, Group A (Oral Iron+rHuEPO) & Group B (I/V Iron+rHuEPO). Informed consent was taken from all patients. Serum ferritin & TIBC were done at the beginning and at the end of the six months. Data was analyzed on SPSS version 16.0 (IBM, Incorporation, USA). The continuous variables were analyzed by student’s t-test. The significant p-value was taken at ≤ 0.05. RESULTS: Significant statistical improvement was observed in Serum Ferritin and TIBC of both Groups (Group A and Group B). But there is more prominent improvement in serum ferritin and TIBC of Group B (I/V iron + rHuEPO). No adverse effects of iron therapy and erythropoietin therapy were observed in patients of both groups. CONCLUSION: The present study concludes that treatment with I/V Iron + Erythropoietin therapy significantly improves Serum Ferritin and TIBC of CRF patients of Group B who received Intravenous Iron Dextran 2ml diluted in 200ml normal saline twice a month + rHuEPO 2000 IU SC twice a week.